Use of menstrual cups among school girls: longitudinal observations nested in a randomised controlled feasibility study in rural western Kenya - Anna Maria van Eijk; Kayla F. Laserson; Elizabeth Nyothach; Kelvin Oruko; Jackton Omoto; Linda Mason; Kelly Alexander; Clifford Oduor; Aisha Mohammed; Alie Eleveld; Isaac Ngere; David Obor; et al. (BMC, 2018)
Abstract Background A menstrual cup can be a good solution for menstrual hygiene management in economically challenged settings. As part of a pilot study we assessed uptake and maintenance of cup use among young school girls in Kenya. Methods A total of 192 girls between 14 to 16 years were enrolled in 10 schools in Nyanza Province, Western Kenya; these schools were assigned menstrual cups as part of the cluster-randomized pilot study. Girls were provided with menstrual cups in addition to training and guidance on use, puberty education, and instructions for menstrual hygiene. During repeated individual visits with nurses, girls reported use of the menstrual cup and nurses recorded colour change of the cup. Results Girls were able to keep their cups in good condition, with only 12 cups (6.3%) lost (dropped in toilet, lost or destroyed). Verbally reported cup use increased from 84% in the first 3 months (n = 143) to 96% after 9 months (n = 74). Colour change of the cup, as 'uptake' indicator of use, was detected in 70.8% of 192 participants, with a median time of 5 months (range 1-14 months). Uptake differed by school and was significantly higher among girls who experienced menarche within the past year (adjusted risk ratio 1.29, 95% CI 1.04-1.60), and was faster among girls enrolled in the second study year (hazard ratio 3.93, 95% CI 2.09-7.38). The kappa score comparing self-report and cup colour observation was 0.044 (p = 0.028), indicating that agreement was only slightly higher than by random chance. Conclusions Objective evidence through cup colour change suggests school girls in rural Africa can use menstrual cups, with uptake improving with peer group education and over time. Trial registration ISRCTN17486946. Retrospectively registered 09 December 2014.